Influence of regional groundwater flow on ground temperature around heat extraction boreholes. (July 2015) - Liuzzo-Scorpo, Alberto; Nordell, Bo; Gehlin, Signhild
Abstract : Highlights: The concept of thermal Influence Length was introduced. The ground temperature distribution around heat extraction boreholes was calculated. Different thermal and hydraulic conductivity of the ground are considered. Effective thermal conductivity was calculated for the same regional groundwater flows. Interpretation of effective thermal conductivity with respect to groundwater flows. Abstract: The increasing popularity of ground-coupled heat pumps has resulted in almost 20% of all Swedish family houses being heated this way. To avoid undesirable interactions between neighboring boreholes and disturbance of the ground temperature, the general rule and recommendation of Swedish authorities is that the distance between two neighboring boreholes must be ≥20 m. However, according to previous studies, relatively low groundwater flow rates may significantly reduce the borehole excess temperature compared to the case of pure heat conduction. In this work the Influence Length is defined and its relations with flow rate, real thermal conductivity of the ground and effective thermal conductivity obtained by thermal response analysis are investigated. The aim of this study was to find a way to use the thermal response test as a means to determine the groundwater flow influence in order to reduce the borehole spacing perpendicular to groundwater flow direction. The results confirm that very low groundwater flow rates are enough to significantly reduce the Influence Length, hence this is a crucial parameter which should be considered. Moreover, a first estimation, even before the thermal response test analysis, of the Influence Length is possible if the knowledge of hydrogeological conditions of the site allows good predictions about real thermal conductivity of the ground and flow rate.